2020
DOI: 10.1029/2019gb006345
|View full text |Cite
|
Sign up to set email alerts
|

A Synthesis of Blue Carbon Stocks, Sources, and Accumulation Rates in Eelgrass (Zostera marina) Meadows in the Northeast Pacific

Abstract: There is increasing urgency to implement climate change mitigation strategies that enhance greenhouse gas removal from the atmosphere and reduce carbon dioxide (CO2) emissions. Recently, coastal “blue carbon” habitats⁠—mangroves, salt marshes, and seagrass meadows—have received attention for their ability to capture CO2 and store organic carbon (OC), primarily in their sediments. Across habitat types and regions, however, information about the sequestration rates and sources of carbon to local sediments remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 69 publications
14
30
1
Order By: Relevance
“…Sediment characteristics are considered the most important factors for carbon storage in Z. marina meadows, whereas seagrass structural complexity and biomass properties, such as canopy height and plant dry weight, have been found to be of minor relevance 14,15,25,31,45 . This also explains why seagrass biomass has a relatively low contribution to the sedimentary organic carbon pool in Z. marina meadows 15,46 and highlights the importance of hydrodynamic exposure and transport of allochthonous organic matter for the carbon sink function in these environments. In fact, seagrass structural complexity influences the hydrodynamic forces by reducing water velocity within the meadow 20 , while at the same time exposure to hydrodynamic forces can influence the meadow properties 27 and morphology of the seagrass plants 28,47 .…”
Section: Discussionmentioning
confidence: 79%
“…Sediment characteristics are considered the most important factors for carbon storage in Z. marina meadows, whereas seagrass structural complexity and biomass properties, such as canopy height and plant dry weight, have been found to be of minor relevance 14,15,25,31,45 . This also explains why seagrass biomass has a relatively low contribution to the sedimentary organic carbon pool in Z. marina meadows 15,46 and highlights the importance of hydrodynamic exposure and transport of allochthonous organic matter for the carbon sink function in these environments. In fact, seagrass structural complexity influences the hydrodynamic forces by reducing water velocity within the meadow 20 , while at the same time exposure to hydrodynamic forces can influence the meadow properties 27 and morphology of the seagrass plants 28,47 .…”
Section: Discussionmentioning
confidence: 79%
“…These average CO 2 evasion/invasion rates are plotted (Figure 4) alongside organic carbon burial rates (CBR) taken from a global literature review (Samper‐Villarreal et al., 2018 [A], Prentice et al., 2020 [B], Duarte et al., 2005 [C], Kennedy et al., 2010 [D], and Sanders et al., 2019 [E]). Converted into the same unit as FCO 2 , these literature CBRs ranged from −0.025 to −0.23 µmol C m −2 s −1 , for a global average of −0.126 ± 0.082 µmol C m −2 s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The coastal ocean plays a disproportionately large role in global and regional carbon (C) cycles (Fennel et al., 2019; Friedlingstein et al., 2019; Laruelle et al., 2018). In particular, seagrass‐inhabited regions receive large quantities of terrestrial and marine organic carbon, much of which is sequestered in sediments and stabilized by extensive root mats (Prentice et al., 2020; Röhr et al., 2018). Carbon fixed locally by seagrasses and their epiphytes is also buried here, constituting a net removal of C from the atmosphere (Duarte et al., 2005; Kennedy et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Significant quantities of carbon can be sequestered by, stored in, and released from seagrass meadows ( Prentice et al, 2020 ). Salinas et al (2020) reported that the loss of seagrass due to human and natural disturbances may have caused the release of 11–21 Tg CO 2 –eq in Australia since the 1950s.…”
Section: Discussionmentioning
confidence: 99%